A Model of Populism as a Conspiracy Theory - Szeidl, Adam; Szucs, Ferenc (American Economic Review, 2025)
We model populism as the dissemination of a false “alternative reality,” according to which the intellectual elite conspires against the populist for purely ideological reasons. If enough voters are receptive to it, this alternative reality—by discrediting the elite's truthful message—reduces political accountability. Elite criticism, because it is more consistent with the alternative reality, strengthens receptive voters' support for the populist. Alternative realities are endogenously conspiratorial to resist evidence better. Populists, to leverage or strengthen beliefs in the alternative reality, enact harmful policies that may disproportionately harm the non-elite. These results explain previously unexplained facts about populism. (JEL D72, D82, D83)